The Significance of Teaching English in Medical Universities (Eurasian Medical Research Periodical, 2023)
This list of literature sources explores the topic of teaching English in medical universities. These sources discuss the importance and impact of English language instruction in medical education, professional development, and patient care. They provide insights into various aspects such as language proficiency, communication skills, cultural competence, and the use of English as a lingua franca in the medical field.